2021
DOI: 10.1038/s41598-021-97890-4
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics maintain the gut microbiome homeostasis during Indian Antarctic expedition by ship

Abstract: Ship voyage to Antarctica is a stressful journey for expedition members. The response of human gut microbiota to ship voyage and a feasible approach to maintain gut health, is still unexplored. The present findings describe a 24-day long longitudinal study involving 19 members from 38th Indian Antarctic Expedition, to investigate the impact of ship voyage and effect of probiotic intervention on gut microbiota. Fecal samples collected on day 0 as baseline and at the end of ship voyage (day 24), were analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
2
2
0
Order By: Relevance
“…During a long-term voyage, seafarers are confronted with various physical and psychological stressors. Consistent with previous reports ( 17 , 18 ), the current study revealed that the gut microbial composition of seafarers was significantly altered after a long-term voyage. Predicted microbial functions, including folate biosynthesis and biotin metabolism, were significantly decreased after the voyage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…During a long-term voyage, seafarers are confronted with various physical and psychological stressors. Consistent with previous reports ( 17 , 18 ), the current study revealed that the gut microbial composition of seafarers was significantly altered after a long-term voyage. Predicted microbial functions, including folate biosynthesis and biotin metabolism, were significantly decreased after the voyage.…”
Section: Discussionsupporting
confidence: 92%
“…Limited studies have explored the impacts of long-term voyages on the intestinal microbiota, and the available studies have used mainly gene sequencing approaches. Zhang et al ( 17 ) and Srivastava et al ( 18 ) found that the intestinal microbiome of seafarers was altered and that multiprobiotics could maintain microbiome homeostasis during long sea voyages. Zheng et al ( 19 ) found that a long-term voyage significantly changed the oral mucosa, skin microbiome composition, and microbial functions of seafarers.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the effect of convergence was stronger in placebo groups compared to groups supplemented with probiotics ( 63 ). This finding is in line with more recent outcomes regarding maintaining GI microbiota eubiosis by probiotics ( 70 ). Furthermore, it is speculated that an enhanced spaceflight diet containing increased quantity and variety of fruits, vegetables, fish and other foods rich in flavonoids and omega-3 fatty acids, preserves community structure in the comparative analysis between pre- and in-mission time points ( 68 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have even highlighted the important effect of diet through the results of their experiments ( 59 ). Besides, the administration of probiotic supplements could be considered as another approach to maintain the gut microbiome homeostasis during the stay in isolated environments ( 70 ).…”
Section: Discussionmentioning
confidence: 99%